Spawning and Reproductive Potential of Blue Swimming Crab (Portunus pelagicus) at Spermonde Archipelago, Indonesia - Muh Saleh Nurdin; Amanda Pricella Putri; Dewi Yanuarita Satari; Riris Yuli Valentine; Fauziah Azmi; Teuku Fadlon Haser (UIN Sunan Gunung Djati Bandung, 2022)
The problem in the management of blue swimming crab (BSC) fisheries is a decrease in stock that overlaps with an increase in fishing activities. This study aimed to analyze the ratio of spawning potential (SPR), reproductive potential, and reproductive productivity of BSCs taken from the Spermonde Islands. Spawning potential was analyzed using SPR, while reproductive potential analysis used the relative proportion of data between female, berried female and the average fecundity of each class size. The results showed that the BSC in Spermonde were growth overfishing and recruitment overfishing. The SPR of the BSC was estimated to be 7%, below the biological reference point. The highest reproductive potential index of berried females occurred in the group with a carapace width of 111-120 mm which contributed 36.84% of the total egg production. The value of reproductive productivity was 1.35 indicating a productive population. Current legislation allows the capture of BSCs with carapace sizes larger than 100 mm. Based on the data of this study, this size limit has the potential to eliminate 65.92% of the total egg production in the Spermonde Islands. To ensure the sustainability of BSCs in the Spermonde Islands, it is necessary to limit size by capturing BSCs >120 mm to protect the berried female and increase total egg production.